Retinitis Pigmentosa in Childhood: A Case Report - Erdal Eren; Ufuk Şahin Tığ; Fadime Kendir; Ali Ayata (Güncel Pediatri)
Retinitis pigmentosa (RP) is characterized by progressive loss of vision and accompanied by many syndromes. Therefore, early diagnosis is very important in RP. Now, definitive treatment of RP is not available. Diagnosis is performed with good medical history and ophthalmolojical examination. We present a patient with RP and describe diagnosis, treatment and approach to this disease. (Journal of Current Pediatrics 2008; 6: 43-6)